Utilização de programa comercial de projetos mecânicos na consolidação das habilidades de projeto de máquinas - Manfrinato, Larissa França Madeira (2015)
The engineering teaching techniques, as well as all courses related to technology are undergoing a major transformation with the advancement of computing resources in all areas. As a training entity of future professionals of this area, it is essential that the Technological University also fits to this new reality. Learning the use of commercial programs is of paramount importance in the formation of the engineer because this skill is required in most of his areas of operation. The purpose of this paper is to show that the use of a commercial software tool can be very interesting also in the consolidation of knowledge in various disciplines, especially in machine design disciplines. Thus, a case study was carried out using the design of a three stage gear reducer which is developed in the traditional way in the discipline of Machine Elements 2 in the course of Mechanical Engineering at UTFPR, to make a comparison with the level of information and computational facilities of the commercial program KISSsoft mechanical designs. The components were recalculated in KISSsoft program and the complete system was created in KISSsys tool, KISSsoft’s complement for complete systems. The results were compared using the safety factor and the most relevant results remained within the expected range, about 20%. With this project it was possible to verify that the computational modeling of machine elements can help in consolidating and deepening of Machine Design’s learning, allowing you to check and interact with aspects of geometry and loading of machine elements. However, being a commercial application program rather than a didactic one, it is not always possible to verify every step of the design and understand the whole program’s calculation chain.